Determinants of Islamic Bank Performance: Board Size and Zakat Disclosure - Rachmadani, Wulan Suci; Aldiansyah, Toufan; Kusuma, Bayu Mitra A.; Malikah, Siti (EQUILIBRIUM, 2026)
This study investigates the determinants of financial performance in Islamic banks by focusing on board diversity and zakat disclosure, addressing the persistent gap between Sharia compliance expectations and actual disclosure practices. While prior research often examines governance and disclosure jointly, evidence on their independent effects remains limited. The purpose of this study is to analyze how governance structures and zakat disclosure individually influence financial performance. A quantitative approach is employed using time series data from 10 Islamic banks in Indonesia over the 2023–2024 period, comprising 80 observations. The data are analyzed using Ordinary Least Squares (OLS) with robust standard errors. The findings reveal that the board of directors has a positive and significant impact on financial performance, highlighting the importance of managerial capacity and strategic decision-making. In contrast, the board of commissioners shows no significant effect, while the Sharia Supervisory Board exhibits a weak negative influence, suggesting its role is more compliance-oriented. Zakat disclosure demonstrates a negative effect on financial performance when measured by Return on Assets, but becomes insignificant under Return on Equity, indicating sensitivity to performance measures. This study concludes that governance effectiveness and Sharia-based disclosure act as distinct drivers of performance. The research contributes to the literature by providing clearer causal insights and offers practical implications for improving governance quality and transparency in Islamic banking.